Prototype Aplikasi PPDB Online Berbasis Web pada SMP Kusuma Bangsa - Adrian Posman Imanuel; Farizi Ilham; Serina Admi Yuliana; Nabila Putri Candra (CV. Shofanah Media Berkah, 2026)
SMP Kusuma Bangsa Tangerang already has web-based information services, but the New Student Admission (PPDB) process still needs improvement so that registration, verification, and prospective student data management can run in a more structured manner. This study aims to design a web-based online PPDB application prototype that enables prospective students to register, complete digital forms, upload documents, obtain an automatic registration number, and monitor admission status. The research applies the prototyping method with data collection techniques consisting of observation, interviews, and literature study. The system was developed using PHP Native, MariaDB, Tailwind CSS, and XAMPP. The result is a web application consisting of school information pages, prospective student accounts, digital forms based on the Student Data Form (F-PD), document upload, user dashboard, admin panel, registration details, and data verification. Functional testing was conducted using Black Box Testing on 35 scenarios, and all tested features produced expected results. Therefore, the prototype can support the school in improving admission service efficiency, reducing data recording errors, and organizing registration data more effectively.